Peningkatan Penerimaan Diri Dengan Layanan Bimbingan Kelompok - Ratu Zhafira Fajri; Yusmansyah Yusmansyah; Shinta Mayasari (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The problem of  this research  was the students who had low self-acceptance. This research aimed to find out whether there was an improvement of the students’s self-acceptance through group guidance services of the eleventh grade students in SMAN 3 Kotabumi academic year 2017/2018. The method of this research was pre-experimental class, and the design was one group pretest-posstest design. The subject of this research was 6 students at the eleventh grade who had low, medium, and high self acceptance. The self acceptance scale was used to collect the data. Different test of Wilcoxon was used to analyze the data. The result showed that the probability value was less than 0.05 (0.0280.05). It could be seen that Ho was rejected and Ha was accepted. It meant that there was a significant improvement of the student’s self-accepted before and after the implementation of group guidance services. It indicated that group guidance services facilitates eleventh grade student’s of SMAN 3 Kotabumi academic year 2017/2018 to improve their self-acceptance.Permasalahan penelitian adalah “Apakah penerimaan diri dapat meningkat melalui layanan bimbingan kelompok”. Tujuan penelitian untuk mengetahui bahwa adanya peningkatan penerimaan diri melalui layanan bimbingan kelompok pada siswa kelas XI SMA Negeri 3 Kotabumi Tahun Pelajaran 2017/2018. Metode penelitian ini adalah metode pre eksperiment dengan desain one-group pretest-posttest design. Subjek penelitian sebanyak 6 siswa SMA yang memiliki penerimaan diri rendah, sedang dan tinggi. Teknik pengumpulan data menggunakan skala penerimaan diri. Hasil analisis data menggunakan uji beda Wilcoxon, diperoleh angka probabilitas kurang dari 0,05 (0,028 0,05) maka Ho ditolak dan Ha diterima, artinya terdapat peningkatan yang signifikan pada penerimaan diri antara sebelum dengan setelah diberi layanan bimbingan kelompok. Kesimpulannya adalah penerimaan diri dapat ditingkatkan melalui layanan bimbingan kelompok pada siswa SMAN 3 Kotabumi Tahun Pelajaran 2017/2018.Kata kunci: bimbingan kelompok, bimbingan konseling, penerimaan diri